Role of shallow electronic traps formed by oxygen vacancies in formation of luminescent properties of CeO₂₋x nanocrystals - Maksimchuk, P.O.; Seminko, V.V.; Bespalova, I.I.; Masalov, A.A. (Functional Materials, 2014)
In the paper methods of thermoluminescence (TSL) and time-resolved spectroscopy were used for investigation of shallow electron traps near edge of 4f⁰ band in CeO₂ and nonstoichiometric CeO₂₋x nanocrystals. It was shown that presence of the electronic traps located about 0.2 eV lower than the bottom of 4f⁰ band leads to sufficient modification of O2p-Ce4f excitation relaxation processes due to excitation retrapping. Strong dependence of TSL signal on the stoichiometry of nanocrystal allows to suppose that electronic defects are associated with oxygen vacancies and are formed by F⁺ centers.